INOVASI LINGKUNGAN: PEMBERDAYAAN SOSIAL MASYARAKAT KAMPUNG PERKOTAAN (STUDI KASUS DI SURABAYA) - Filipus Priyo Suprobo; Ririn Dina Mutfianti (Fakultas Seni Rupa dan Desain ITB, 2021)
The leading kampung in the city of Surabaya has become a self-supporting social entity with a hybrid organizationalfunction. This has made Surabaya one of the Global Green Cities in 2017. These kampungs in Surabaya carry outcommunity empowerment independently in their function to complement or balance the government functions. Theempowerment puts forward social functions based on environmental innovation in creating commercial goals that provide benefits for its members. This study aims to find the determinants of environmental innovation resulting from social empowerment of urban village communities with a qualitative approach. The researcher acts as an instrument withsix sources from five selected leading kampungs: Mangrove Kampung, Bratang Binangun Kampung, Grudo Kampung,Maspati Kampung, and Jambangan Kampung. Data were collected through field observations and document searches forapproximately two months from August to September 2019. The analysis and validation were processed by triangulation,checking group members, and rich descriptions of the essence of environmental innovation in the city of Surabaya.